The assignment of the configuration for α-hydroxy acid esters using a CEC strategy. Issue 23 (18th May 2016) - Peng, Ruixue; Lin, Lili; Zhang, Yuheng; Wu, Wangbin; Lu, Yan; Liu, Xiaohua; Feng, Xiaoming
Abstract : A simple and efficient 1 H NMR method for determining the absolute configuration of chiral α-hydroxy acid esters using a CEC strategy with a chiral N, N ′-dioxide-scandium(iii ) complex was developed. Abstract : A simple and efficient 1 H NMR method for determining the absolute configuration of chiral α-hydroxy acid esters using a competing enantioselective conversion (CEC) strategy was developed. The α-hydroxy acid esters were acylated in the presence of Feng's chiral N, N ′-dioxide–scandium(iii ) complex, and the faster reaction was identified when one enantiomer of the chiral α-hydroxy acid ester was treated with both enantiomers of the ligand by NMR analysis of the reaction mixture without further purification. A mnemonic is presented to aid the assignment of the absolute configuration of the substrates.